Biedne zwierzęta patrzą na ludzi. Na marginesach książki Piotra Krupińskiego „Dlaczego gęsi krzyczały?” Zwierzęta i Zagłada w literaturze polskiej XX i XXI wieku - Markiewicz, Miłosz (Zoophilologica. Polish Journal of Animal Studies, 2017)
The article presents a reflection on the presence of animals in the Holocaust and in the narratives that underpinned it. The starting point of this consideration is the book by a Polish literary scholar – Piotr Krupiński „Why did the Geese Shriek?” Animals and the Holocaust in Polish Literature of the 20th and 21st Century. The author juxtaposes the book with the comic book Maus by Art Spiegelman and the nazi propaganda film The Eternal Jew. The article raises questions about, among others, suffering of animals, a human–animal dualism in the context of the Holocaust, zoomorphism, and controversies over the so called animal holocaust. The author points out that we should remember the human is also an animal, especially at the time of the reflection on the Holocaust, which reveals the issue of „community of death”.